COVID-19 cases before and after the “I Stay at home” decree, Bologna Local Health Authority, Italy - Stivanello, Elisa; Perlangeli, Vincenza; Resi, Davide; Marzaroli, Paolo; Pizzi, Lorenzo; Pandolfi, Paolo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: Various measures have been taken by the Italian Government to contain and mitigate the COVID-19 outbreak and on March 11th a decree called “I stay at home” put the whole nation under lockdown. Our aim is to describe sociodemographic and transmission profile of COVID-19 cases that were transmitted before and after the introduction of the decree in the Bologna Local Health Authority. Methods: Cases were classified as transmitted before or after the decree according to the date of last contact with a COVID-19 case or, if this date was unavailable, we used the date of onset of symptoms considering the incubation period. Sociodemographic, clinical and epidemiological information was collected by using the infectious disease monitoring database, hospital discharge, deprivation index and long term care facility databases. Results: In the period after the publication of the decree, there were more elderly, females, strangers, retired, residents in nursing homes and deprived people than in the first period. There were also more health care personnel and less professionals/managers, sales or office workers. In both phases, family is mentioned as the first community attended although less frequently in the second group. Conclusions: The profile of the new COVID-19 cases changed during the outbreak suggesting a differential effect of lockdown measures on the population. An equity lens should be used when analyzing the impact of pandemia and the measures taken to curb it.